2008
DOI: 10.1038/mp.2008.14
|View full text |Cite
|
Sign up to set email alerts
|

A high-density SNP genome-wide linkage scan in a large autism extended pedigree

Abstract: We performed a high-density, single nucleotide polymorphism (SNP), genome-wide scan on a six-generation pedigree from Utah with seven affected males, diagnosed with autism spectrum disorder. Using a two-stage linkage design, we first performed a nonparametric analysis on the entire genome using a 10K SNP chip to identify potential regions of interest. To confirm potentially interesting regions, we eliminated SNPs in high linkage disequilibrium (LD) using a principal components analysis (PCA) method and repeate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 63 publications
6
53
0
Order By: Relevance
“…7 The current sample includes this original pedigree, but these regions were not strongly supported by the new pedigrees. Within these 70 pedigrees, our strongest signals in any of these previous regions were on chromosomes 9p24.3 (HLOD=1.30 at 2,202,546 bp) and 20q11.21-q13.12 (HLOD=1.23 at 40,018,916 bp), but both of these regions were below the suggestive linkage threshold.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…7 The current sample includes this original pedigree, but these regions were not strongly supported by the new pedigrees. Within these 70 pedigrees, our strongest signals in any of these previous regions were on chromosomes 9p24.3 (HLOD=1.30 at 2,202,546 bp) and 20q11.21-q13.12 (HLOD=1.23 at 40,018,916 bp), but both of these regions were below the suggestive linkage threshold.…”
Section: Resultsmentioning
confidence: 82%
“…7 In this previous study, we identified three chromosomal regions meeting genome-wide linkage significance criteria at 3q13.2-13.31, 3q26.31-q27.3, and 20q11.21-q13.12; and two additional regions meeting criteria for suggestive significance at 7p14.1-p11.22 and 9p24.3. All five identified regions replicated previous findings, and for some of the regions, we were able to narrow the boundaries.…”
Section: Introductionmentioning
confidence: 83%
“…126 In contrast with these disorders, there has been no strong evidence for linkage on chromosome 8p in any of the genome-wide linkage studies of autism. 127,128 Only one linkage analysis on multiplex autism families stratified according to delayed expressive speech found higher linkage signals in the delayed groups for some loci on chromosome 8p. 129 Given this linkage scenario, chromosome 8p should be considered as a robust candidate for a susceptibility region for schizophrenia especially with clinical features that bring to mind the classical dementia-praecox syndrome described by Emil Kraepelin.…”
Section: Chromosome 8p Neuropsychiatric Disorders and Cancermentioning
confidence: 99%
“…The disruption of gene products that are highly expressed in Purkinje neurons is also associated with movement disorders including cerebellar ataxia (43) and is compatible with our finding that DLGAP4 gene products (mRNAs and protein) were abundant in human Purkinje neurons. Additionally, single nucleotide polymorphisms within the 20q11.21–q13.12 locus and comprising the DLGAP4 gene have been linked with the development of early onset autism spectrum disorders (44,45). Moreover, altered methylation patterns have been found in three CpG islands within the SHANK3 gene (coding for the SH3 and ankyrin domain containing protein, a known interaction partner of DLGAP4) (40), in post-mortem brain samples from autism spectrum disorder patients, which is accompanied with altered expression and alternative splicing of the SHANK3 gene (22).…”
Section: Discussionmentioning
confidence: 99%